Breast cancer bone metastasis and bone metastatic cells retain NKG2DLs intracellularly: could this be a strategy to evade immune recognition? - Gomarasca, Marta; Maroni, Paola; Verdelli, Chiara; Gerosa, Laura; Faraldi, Martina; Luzzati, Alessandro; Cannavò, Luca; Banfi, Giuseppe; Lombardi, Giovanni (Frontiers in Cell and Developmental Biology, 2026)
Bone metastases dramatically worsen breast cancer (BC) prognosis reducing overall survival. Natural killer (NK) cells recognize and eliminate malignant cells through the interaction with NKG2D receptor ligands (NKG2DLs) on cancer cells. Tumors often evade NK surveillance by downregulating the NKG2DLs expression and avoid recognition, but whether this occurs in bone metastases remains unclear. This study investigates mechanisms of NKG2DLs downregulation in primary BC and bone metastases (BoMet). Expression and localization of the NKG2D/NKG2DL axis components were investigated in BC tissues (with and without metastases), paired bone metastatic ductal carcinoma (bmDC), BoMet, and in BC cells lines of varying invasiveness. In bmDC and BoMet, major histocompatibility complex class I chain-related protein A and B (MICA/B) and UL16-binding protein 2 (ULBP2) localized in perinuclear area, contrasting with predominantly cytosolic distribution in non-metastatic BC. Similarly, invasive MDA-MB-231 and MDA-BoM-1833 showed NKG2DLs perinuclear localization and co-localization with the Golgi apparatus, while less invasive MCF7 showed a prominent cytosolic distribution. Accumulation of NKG2DLs in membrane and cytoskeletal fractions further supports this pattern. Additionally, when N-glycosilation is impaired, NKG2DLs fail to reach the cell surface in metastatic cell lines, while are still transported through the Golgi apparatus and delivered to the plasma membrane, resulting in increased surface expression irrespective of correct glycosylation. Our findings suggest that invasive and bone-metastatic breast cancer cells are more dependent on correct glycosylation and intracellular trafficking for NKG2DL surface expression than non-metastatic breast cancer cells. This difference may have important implications for potential immune evasion mechanisms and for the development of therapeutic strategies targeting bone metastases in breast cancer.